Codifying Choice of Law Around the World : an International Comparative Analysis - Symeonides, Symeon, 1949- (Oxford University Press, USA, 2014)
Codifying Choice of Law Around the World chronicles, documents, and celebrates the extraordinary, massive codification of Private International Law (PrIL), or Conflict of Laws that has taken place in the last 50 years, from 1962-2012. During this period, the world has witnessed the adoption of nearly 200 PrIL codifications, EU Regulations, and international conventions--more than in all preceding years since the inception of PrIL. This book provides a horizontal comparison and discussion of these codifications and conventions, first by comparing the way they resolve tort and contract conflict.